2004
DOI: 10.1161/01.cir.0000142048.94084.ca
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cardiovascular Risk as Predicted by Established Risk Scores Versus Plaque Progression as Measured by Serial Intravascular Ultrasound in Left Main Coronary Arteries

Abstract: There was a positive linear relationship between the estimated risk of clinical events derived from all 3 established risk-score algorithms and the extent of plaque progression measured by serial IVUS. This translated into stenosis progression (reduction in lumen dimensions) with increasing clinical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
9

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 23 publications
3
74
0
9
Order By: Relevance
“…In a study of 107 patients with angiographically insignificant coronary atherosclerosis, left main coronary artery disease detected by IVUS was significantly associated with future coronary events 63 . IVUS studies have shown that the rate of plaque growth in the left main coronary artery correlates with traditional risk factors 64,65 . Patients at greatest risk of cardiovascular events, as determined by the PROCAM, SCORE, and Framingham CVD algorithms, exhibited significantly greater plaque progression between baseline and follow-up (median 14 months).…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%
“…In a study of 107 patients with angiographically insignificant coronary atherosclerosis, left main coronary artery disease detected by IVUS was significantly associated with future coronary events 63 . IVUS studies have shown that the rate of plaque growth in the left main coronary artery correlates with traditional risk factors 64,65 . Patients at greatest risk of cardiovascular events, as determined by the PROCAM, SCORE, and Framingham CVD algorithms, exhibited significantly greater plaque progression between baseline and follow-up (median 14 months).…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%
“…To date, quantitative studies of human coronary atherosclerosis in patients with diabetes have provided conflicting information [2][3][4][5]. Also, while individuals with impaired fasting glucose (IFG) tolerance have an increased cardiovascular risk [6], the severity and progression of coronary atherosclerosis in this group have not been compared with that in patients with and without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a validated risk score for secondary prevention, established primary-event risk scores have already been used to assess the relations between predicted cardiovascular risk and (1) the extent of plaque progression as assessed with serial intravascular ultrasound [29], and (2) the extent of coronary calcifications in patients with a first MI [30]. Notably, in the latter study by Pohle et al, which also investigated patients with a first MI, the estimated 10-year event risk as calculated by the Framingham Risk Score (14.3 ± 4.4%) was similar to that of our study (14.1 ± 5.8% ((i.e.…”
Section: Discussionmentioning
confidence: 99%